Public Libraries Platform - Ahmet Uğur Özçelik; Şaban Aksoy; Hakan Yücel; Mehmet Küçük (Türk Kütüphaneciliği)
In the article, the Public Libraries Platform, which is formated by a group of public librarians, is introduced for the purpose of taking an initiative to discuss the problems of public libraries and seek solutions.